Frozen Section Library: Head and Neck - Zhai, Qihui Jim.; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
Frozen sections are performed while a patient is undergoing surgery as a basis for making an immediate diagnosis that will impact treatment decisions. Frozen section diagnosis is often a highly demanding situation for the pathologist who must render a diagnosis quickly for the patient and surgeon. The Frozen Section Library series will provide concise, user-friendly, site specific handbooks that are well illustrated and highlight the pitfalls, artifacts and differential diagnosis issues that arise in the hurried frozen section scenario. Qihui "Jim" Zhai, MD, FCAP, is Professor of Pathology, University of Cincinnati, Cincinnati, OH. He is also Attending Pathologist at Greater Cincinnati Pathologists, Inc., Cininnati, OH.
General Considerations -- Diseases by Anatomiv Site -- Nsal Cavity and Paranasal Sinuses -- Salivary Glands -- Oral Cavity, Pharynx, and Larynx -- Head -- Head and Neck Presentations of Intracranial Lesions -- Suggested Reading -- Index.
Keywords: MEDICINE; NEUROLOGY; PATHOLOGY; SURGERY; MEDICINE & PUBLIC HEALTH; PATHOLOGY; SURGERY; NEUROLOGY